Penguatan Paradigma Kewirausahaan bagi Purna Pekerja Migran Indonesia di wilayah Jawa Timur dan Nusa Tenggara Barat - E Rizky Wulandari; Eka Handayani; Meithiana Indrasari; Anita Agustina Wulandari; Eko Pamuji (Prapanca : Jurnal Abdimas, 2023)
Placement of Indonesian Migrant Workers (PMI) experienced a downward trend throughout 2014-2019. Their welfare level has decreased compared to when they were still working abroad. Ex-migrant workers face complex problems after completing their work contracts and returning to their homeland. The transformation of consumptive to productive behavior and the use of digital technology are the keywords for the service team to hold entrepreneurial training activities for former PMIs. Digital technology has now become an integral part for all levels of society, especially the former PMI. Service activities are carried out based on a curriculum that has been prepared with materials adapted to the conditions of the target community. The training method is offline activities for 4 days with a total of 32 meetings. The results obtained from the training are that the Implementation of Training and Practice on Digitizing Business Processes for Indonesian Ex-Migrant Worker Business Groups with the Theme of Digital Marketing for the community of ex-migrant Indonesian business actors that has been carried out with a meeting curriculum arrangement is able to provide new insights and understanding for participants to be able to compete. globally in their respective business sectors. It was explained that 68% of participants considered that the material was relevant to the problems faced by the participants and that the benefits of the training could be judged to have an appropriate level of sustainability to continue to be implemented.